Different profiles and epidemiological scenarios: Past, present and future - Gorla, David Eladio (2021)
The multiplicity of epidemiological scenarios shown by Chagas Disease, derived from multiple transmission routes of the aetiological agent, occurring on multiple geo-ecobiosocial settings determines the complexity of the disease and reveal the difficulties for its control. From the first description of the link between the parasite, the vector and its domestic habitat and the disease that Carlos Chagas made in 1909, the epidemiological scenarios of the American Trypanosomiasis has shown a dynamic increasing complexity. These scenarios changed with time and geography because of new understandings of the disease from multiple studies, because of policies change at the national and international levels and because human movements brought the parasite and vectors to new geographies. Paradigms that seemed solid at a time were broken down, and we learnt about the global dispersion of Trypanosoma cruzi infection, the multiplicity of transmission routes, that the infection can be cured, and that triatomines are not only a health threat in Latin America. We consider the multiple epidemiological scenarios through the different T. cruzi transmission routes, with or without the participation of a Triatominae vector. We then consider the scenario of regions with vectors without the parasite, to finish with the consideration of future prospects.